Budesonide increases TLR4 and TLR2 expression in Treg lymphocytes of allergic asthmatics. (June 2015) - Pace, Elisabetta; Di Sano, Caterina; Ferraro, Maria; Bruno, Andreina; Caputo, Valentina; Gallina, Salvatore; Gjomarkaj, Mark
Abstract: Background: Reduced innate immunity responses as well as reduced T regulatory activities characterise bronchial asthma. Objectives: In this study the effect of budesonide on the expression of TLR4 and TLR2 in T regulatory lymphocyte sub-population was assessed. Methods: TLR4 and TLR2 expression in total peripheral blood mononuclear cells (PBMC), in CD4+/CD25+ and in CD4+/CD25− was evaluated, by flow cytometric analysis, in mild intermittent asthmatics ( n  = 14) and in controls ( n  = 11). The in vitro effects of budesonide in modulating: TLR4 and TLR2 expression in controls and in asthmatics; IL-10 expression and cytokine release (IL-6 and TNF-α selected by a multiplex assay) in asthmatics were also explored. Results: TLR4 and TLR2 were reduced in total PBMC from asthmatics in comparison to PBMC from controls. CD4+CD25+ cells expressed at higher extent TLR2 and TLR4 in comparison to CD4+CD25− cells. Budesonide was able to increase the expression of TLR4, TLR2 and IL-10 in CD4+/CD25highly+ cells from asthmatics. TLR4 ligand, LPS induced Foxp3 expression. Budesonide was also able to reduce the release of IL-6 and TNF-α by PBMC of asthmatics. Conclusions: Budesonide potentiates the activity of Treg by increasing TLR4, TLR2 and IL-10 expression. This event is associated to the decreased release of IL-6 and TNF-α in PBMC treated with budesonide. These findings shed light on new mechanisms by which corticosteroids, drugs widely used for the clinical management of bronchial asthma, control T lymphocyte activation.